Ibadah Online sebagai Gaya Hidup: Sebuah Kajian Teologi Moral terhadap Konsumerisme di Tengah Pandemic Covid – 19 - Nayuf, Henderikus (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
This paper intends to examine online worship which is the choice for religious people (Christians), when Covid-19  attacks the religious mindkind. At first the choice to worship online presented pros and cons. However, after that, online worship (online) became a model that replaced offline worship. This artikel using a phenomenological-descriptive analisys approach, it was found that online worship is part of the embrace of globalization which then presents the spirit of consumerism. Therefore, we need to look at this phenomen from the perspective of moral theology. This important,  so that we se the reality that is happening wisely.